Obstetric perineal trauma: a modern view of the problem. A prospective study - Liliya R. Toktar; Mekan R. Orazov; Kseniya I. Li; Veranika E. Pak; Irina A. Samsonova; Mikhail V. Krestinin (IP Berlin A.V., 2022)
Trauma to the perineum during childbirth is still a common obstetric problem. The question of etiology and risk factors is still extremely debatable. The high risk of long-term consequences of perineal injuries creates the need for timely prediction and effective prevention of this complication of childbirth, which seems to be the main reserve for reducing future pelvic floor insufficiency and associated pathological conditions. Background. Perineal trauma during childbirth is still a common problem in obstetrics. Also, a high percentage of long-term consequences of perineal injuries creates the need for timely prediction and effective prevention of perineal trauma during childbirth, which is relevant today. Aim. To identify the main predictors of the risk of developing obstetric perineal injury. Materials and methods. We conducted a prospective randomized study between September 2020 and January 2022, which included 110 pregnant women. The observation of the patients began from the day of the first visit to the antenatal clinic and throughout pregnancy and the postpartum period, much attention was paid to a comprehensive perineological examination. Results. In group 1, a large number of grade I and II tears (n=37, 33% and n=24, 29%) were noted, and grade III tears were completely absent. In group 2, there were grade III perineal tears, the frequency was (n=5, 2.1%), but still their number was inferior to grade I and II tears (n=10, 26% and n=15, 14%). In group 3, the analysis showed a low frequency of perineal tears of I and II degrees (n=8, 11% and n=17, 18%) and a number of tears of degree III comparable to group 2 (n=8, 2.6%). Episiotomy in all groups was carried out in the range from 7 to 9%, strictly according to obstetric indications. Conclusion. According to the data obtained, the most significant clinical and anamnestic predictors of obstetric perineal trauma were: frequent abortions in anamnesis, chronic diseases of the ENT organs and the urinary system, vaginal dysbiosis (nonspecific vaginitis, bacterial vaginosis), changes in the pH of the vaginal environment, low tone of the perineum, the presence of scar on the perineum.